A comprehensive study of space vector pulse‐width modulation technique for three‐phase Z‐source inverters. (29th April 2015) - Yu, Kun; Xiong, Binyu; Zhao, Jiyun
Summary: The space vector pulse width modulation (SVPWM) technique has received much attention for three‐phase Z‐source inverters (ZSIs). The differences and connections between the SVPWM technique for ZSIs and for traditional voltage source inverters have been discussed as well. By selecting different null state and shoot‐through state, three switching patterns with different switching numbers have been studied, and the harmonic spectrums of these three patterns are demonstrated. In this paper, the solutions of maximum boost control and constant boost control methods using SVPWM techniques with less switching actions have been proposed and compared with the carrier‐based strategies. Selected experimental results have been provided to validate the theoretical analysis. This work will be beneficial for understanding the SVPWM concept and modulation techniques of the three‐phase ZSIs. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The space vector pulse width modulation (SVPWM) technique has been received much attention for three‐phase Z‐source inverters (ZSIs). The differences and connections between the SVPWM technique for ZSIs and for traditional voltage source inverters have been discussed as well. By selecting different null state and shoot‐through state, three switching patterns with different switching numbers have been studied and the harmonic spectrums of these three patterns are demonstrated. In this paper, the solutions of maximum boost control and constant boost control methods using SVPWM techniques with less switching actions have been proposed and compared with the carrier‐based strategies. Selected experimental results have been provided to validate the theoretical analysis. This work will be beneficial for understanding the SVPWM concept and modulation techniques of three‐phase ZSIs.